Gated communities from the perspective of developers - Tüzin Baycan-Levent; Aliye Ahu Gulumser (European Regional Science Association (ERSA), 2005)
Gated housing areas have increasingly become a profitable segment in the real estate market as well as a new marketing angle for developers to meet the demand for security, status/prestige, and lifestyle. The development patterns of gated communities in many countries show that developers recognize the opportunity to sell safety and security to a niche market. Against this background, the aim of this paper is to investigate the development process of gated communities in a metropolitan city, Istanbul, from the perspective of developers. The data and information used for evaluation are based on the extensive survey questionnaires filled out by developers of gated communities. A "logistic regression method” is deployed to identify the most important factors on approaches and behaviors of developers. Therefore, the motivating factors both in the decision-making and production-marketing process of developers are evaluated. This evaluation enables us to highlight the characteristics of the real estate market.
Keywords: 330